GAMBARAN ANGKA KESEMBUHAN PASIEN TUBERKULOSIS (TB) PARU DI RUMAH SAKIT UMUM DAERAH PETALA BUMI PEKANBARU PERIODE JANUARI 2011-DESEMBER 2013 - Atika, Imelda (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTPulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis which can be cured and prevented. Cured is patient who wan completed treatment with sputum smear-negatif in the last month of treatment and on at least one previous occasion.The aim of this research is to recognize the cure rate of pulmonary tuberculosis patient in Petala Bumi hospital of Pekanbaru. The research design was desriptive using retrospective approach. This research was conducted of ward patients and TB-01 form. Sample collected from 29 patients that included in inclusion criteria. The result showed that patients of pulmonary tuberculosis declared cured in lung department of petala bumi hospital of Pekanbaru showed large proportion in the productive group 15-54 years (89,65%), the most gender is male (62,07%), most work is entrepreneur (65,51%), most education level is senior high school (41,38%), most increasing of weight (86,20%), most drugs swallowing control (PMO) is any PMO (96,55%), and most regularity of taking medicine is unregularity (100%).Keywords: tuberculosis (TB), cure rate